Dhaka Metropolitan Development Plan : Strategic Environmental Assessment - World Bank (World Bank, Washington, DC, 2021)
Dhaka is one of the ten mega-cities in the world. Growing at a very fast rate, the population of Dhaka urban area is predicted to increase to about 21 million by 2015 from the current population of 11.3 million. Dhaka's rapid development, its fast-changing urban landscape and the associated critical environmental challenges call for holistic urban planning, strengthening of institutions responsible for urban development and good governance. Rapid urbanization has raised two sets of environmental challenges in Dhaka. The first arises from specific urban development investments which treat potential environmental effects as externalities. The second set of broad range of environmental issues stem from pressure on water and land resources and indiscriminate use/misuse of these resources. The Strategic Environment Assessment (SEA) is a decision making tool being used for the first time by the Government of Bangladesh to strategize and provide direction to the preparation and implementation of the Detailed Area Plans (DAPs). It is also a key policy instrument which will enable the World Bank to conduct a focused policy dialogue, provide recommendations for institutional strengthening and address political economy governance concerns in the context of the implementation of DAPs in the Dhaka metropolis. Principal reasons for this slow development of the DAP formulation process are: the lack of higher level planning strategy; and over-ambitious terms of reference, poor process design and inadequate allocation of technical resources by Rajdhani Unnayan Katripakkha (RAJUK).